P049 Age-associated B cells in early drug-naÏve rheumatoid arthritis patients. (March 2019) - Vidal Pedrola, G; Pratt, A; Mellor, A; Scheel-Toellner, D; Isaacs, J; Anderson, A
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterised by joint inflammation and bone destruction. The presence of autoantibodies, years before the clinical onset of disease, and the efficacy of Rituximab, a B-cell depleting therapy, highlight a pathogenic role for B cells. Different groups have recently identified a novel subset of B cells named age-associated B cells (ABCs). Studies in mice autoimmune models and patients suffering from autoimmune diseases described these cells as CD19 high CD21 - CD11c + . Moreover, a subset of synovial fluid B cells with low levels of CD21, expresses FcRL4 and produces the cytokine RANKL, which stimulates the differentiation and activation of osteoclasts. The ABCs found in peripheral blood could therefore be the precursors of this FcRL4 positive subset found in synovia. Objectives: We aimed to investigate the proportion and phenotype of peripheral blood ABCs in patients suffering from early drug naïve RA. Methods: Newly presenting patients, naïve to immunomodulatory treatment, were recruited from the Newcastle Early Arthritis Clinic, and followed until diagnoses were confirmed. B-cell subsets in peripheral blood were detected and phenotyped using flow cytometry. NanoString nCounter Immunlogy v2 Panel (NanoString Technologies) was used to detect mRNA from cell lysates of sorted ABCs, naïve, memory and CD5+ B cells from RA patients, age-matched healthy controls and disease controls (Psoriatic Arthritis patients). Results: Our work showed that there are no significant differences in the frequency of ABCs between RA patients, disease controls and age-matched healthy controls. There is a possible trend for increased frequencies of ABCs with age as well as those who have a high disease activity. Our results also show that ABCs resemble a memory B cells phenotype with regard to class-switch immunoglobulins expression, with a significant percentage of them being positive for IgG and IgA. Interestingly, the FcRL4 +, the proliferating Ki67 + and the T-bet expressing B cells were enriched in the ABC population compared to the other B cell subsets. Furthermore, ABCs expressed high levels of MHC class II and co-stimulatory molecules, as well as the activation marker, CD69. In addition, gene expression analysis using NanoString showed differentially expressed genes between ABCs and memory B cells. Conclusions: These data supports an activated phenotype of the ABCs, which supports the idea that ABCs have a pathogenic role in RA, potentially via autoantibody and T cell stimulatory ability. However, further characterisation of this subset and functional studies are needed. Disclosure of Interest: None declared.